Pengaruh Compensation dan Motivation Terhadap Employee Performance PTPN VIII Parakan Salak - Abdul Aziz; Ferinda Rahayu Aglesia (Institut Manajemen Wiyata Indonesia, 2020)
This study aimed to determine: (1) the impact of compensation on employee performance, (2) motivation on employee performance, and (3) the impact of compensation and motivation simultaneously on employee performance. The subjects of this research are employees in PTPN VIII Parakan Salak Plantations. The number of respondents in this study are 100 people. The method of collecting data through a survey using a questionnaire. The data analysis technique used in this study is Multiple Linear Regression Analysis. The results showed (1) compensation did not affect employee performance, (2) motivation affects employee performance, 3) simultaneously compensation and motivation affect significant employee performance.